2020
DOI: 10.1126/science.aaz8043
|View full text |Cite
|
Sign up to set email alerts
|

Phonon hydrodynamics and ultrahigh–room-temperature thermal conductivity in thin graphite

Abstract: Allotropes of carbon, such as diamond and graphene, are among the best conductors of heat. We monitored the evolution of thermal conductivity in thin graphite as a function of temperature and thickness and found an intimate link between high conductivity, thickness, and phonon hydrodynamics. The room-temperature in-plane thermal conductivity of 8.5-micrometer-thick graphite was 4300 watts per meter-kelvin—a value well above that for diamond and slightly larger than in isotopically purified graphene. Warming en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 37 publications
4
90
0
1
Order By: Relevance
“…9 . v u is about twice as large as v in diamond, the highest speed of sound measured at ambient conditions [the in-plane speed of sound in graphite is slightly above v in diamond ( 10 )].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 . v u is about twice as large as v in diamond, the highest speed of sound measured at ambient conditions [the in-plane speed of sound in graphite is slightly above v in diamond ( 10 )].…”
Section: Resultsmentioning
confidence: 99%
“…We support this result with a large set of experimental data for different systems and the firstprinciples modeling of atomic hydrogen. Identifying and understanding bounds on physical properties is important from the point of view of fundamental physics, predictions for theory and experiment, and searching for and rationalizing universal behavior [see, e.g., (3)(4)(5)(6)(7)(8)(9)(10)(11)]. Properties for which bounds were recently discussed include viscosity and diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using the iterative BTE method, (Lee et al, 2015a) found that there is an obvious hydrodynamic phonon transport in graphene over a wide temperature range due to the presence of strong N scattering processes. Subsequently, (Machida et al, 2020) experimentally showed an extremely high thermal conductivity in the very thin graphite samples (8.5-micrometer-thick) at higher temperature, which extends the hydrodynamic regime from cryogenic to room temperatures. That is, there are three phonon transport behaviors, namely ballistic, diffusive and hydrodynamic transport.…”
Section: Graphenementioning
confidence: 89%
“…In principle, the larger the ordered crystalline domain holds, the better the performance of fibers should be, approaching the extreme case of single‐crystalline graphite whiskers. [ 12,13 ] The central mission in fabricating qualified GFs is to fashion graphene sheets into a highly crystalline order with giant and aligned crystallites. Notably, improper microstructures, like incompact stack of graphene and misaligned arrangement, still prevail in previously reported GFs, and bring poor crystallization and thus limited properties.…”
Section: Introductionmentioning
confidence: 99%